Antifungal and antiaflatoxigenic assessment of new Cu(II)–pq complexes against Aspergillus parasiticus, in dark conditions and under visible irradiation. Issue 19 (1st November 2021) - Lioli, Eutuxia; Kollia, Eleni; Markaki, Panagiota; Mitsopoulou, Christiana A
ABSTRACT: The issue of food contamination by fungi and aflatoxins; constitutes a serious concern not only for human/animal health but also for agriculture and the economy. Aflatoxins are secondary metabolites produced by certain filamentous fungi and contaminate a variety of foodstuffs. In this context, control of fungal growth and aflatoxin contamination appears to be important. The present study aimed to investigate new Cu(I) and Cu(II)–quinoxaline complexes, namely [Cu(2, 2´-pq)(NO3 )](NO3 ) (1), [Cu(2, 2´-pq)2 (NO3 )](NO3 )·6H2 O (2) and [Cu(2, 2΄-pq)2 ](BF4 ) (3), where 2, 2´-pq is 2-(2'-pyridyl quinoxaline), as antifungal agents against Aspergillus parasiticus . All complexes, the ligand and the starting material Cu(NO3 )2 –3H2 O, regardless of the concentration used, caused inhibition of A. parasiticus growth ranged from 8.52 to 33.33%. The fungal growth inhibition was triggered when irradiation in visible (λ > 400 nm) was continuously applied (range 18.36–57.20%). The highest inhibitory activity was exhibited by the complex [Cu(2, 2´-pq)2 (NO3 )](NO3 )·6H2 O and for this reason, it was selected to be studied for its ability to suppress aflatoxin B1 produced by A. parasiticus . AFB1 production after the irradiation process was found to be suppressed by 25% compared to AFB1 produced in dark conditions. Abstract : Cu(II)–pq complexes suppress Aspergillus parasiticus growth under dark conditions and under visible irradiation.